Time-to-completed-imaging, survival and function in patients with spinal epidural abscess: Description of a series of 34 patients, 2015-2018 - Caroline King; Cameron Fisher; Patrick C. M. Brown; Kelsey C. Priest; Mary Tanski; Peter Sullivan (BMC, 2020)
Abstract Introduction Spinal epidural abscess (SEA) is a rare and life-threatening infection with increasing incidence over the past two decades. Delays in diagnosis can cause significant morbidity and mortality among patients. Objective The objective of this study was to describe trends in time-to-imaging and intervention, risk factors, and outcomes among patients presenting to the emergency department with SEA at a single academic medical center in Portland, Oregon. Methods This retrospective cohort study analyzed data from patients with new SEA diagnosis at a single hospital from October 1, 2015 to April 1, 2018. We describe averages to time-to-imaging and interventions, and frequencies of risk factors and outcomes among patients presenting to the emergency department with SEA. Results Of the 34 patients included, 7 (20%) died or were discharged with plegia during the study period. Those who died or were discharged with plegia (n = 7) had shorter mean time-to-imaging order (20.8 h versus 29.2 h). Patients with a history of intravenous drug use had a longer mean time-to-imaging order (30.2 h versus 23.7 h) as compared to those without intravenous drug use. Patients who died or acquired plegia had longer times from imaging completed to final imaging read (20.9 h versus 7.1 h), but shorter times from final imaging read to surgical intervention among patients who received surgery (4.9 h versus 46.2 h). Further, only three (42.9%) of the seven patients who died or acquired plegia presented with the three-symptom classic triad of fever, neurologic symptoms, and neck or back pain. Conclusions SEA is a potentially deadly infection that requires prompt identification and treatment. This research provides baseline data for potential quality improvement work at the study site. Future research should evaluate multi-center approaches for identifying and intervening to treat SEA, particularly among patients with intravenous drug use.